PRINCIPLES OF PERSONNEL MOTIVATION AND CORPORATE VALUES OF THE IKEA COMPANY - Alexander V. Butov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies motivation principles of the IKEA company, including the importance of work being done, recognition and awarding the results, trust in employees, their unity and consolidation, possibility to study, develop and be promoted and absence of short-term optional programs for executives. Special attention is paid to the most important element of the motivation system, i. e. its sound corporate culture, whose components (encouraging mission statement and corporate values) are as  significant for employees as the system of material incentives.  Research findings allow us to estimate the efficiency of key factors of the company successful development – the motivation system and  corporate culture of the IKEA company and provide an opportunity to use its advanced experience by Russian trade companies.